Research Note: Job Satisfaction and Working From Home in Romania, Before and During COVID-19 - Țălnar-Naghi, Dana Ioana (Calitatea Vieții, 2021)
Based on ICTs development, telework is a rapidly changing phenomenon (Eurofound, 2017) and has provoked many debates on how it influences people's lives (Allen, Golden and Shockley, 2015; Golden, 2009), allowing people to work from anywhere and anytime via laptops, tablets, and smartphones (Maitland and Thomson, 2014). The Covid-19 outbreak accelerated social change and led to a forced entry of entire segments of the workforce into telework. The change was steep in particular for countries with a lower pre-pandemic incidence of working from home, such as Romania. Using longitudinal data from an original series of surveys (Voicu et al. 2020) carried out in 2018 and during the Spring 2020 lockdown in Romania, the paper aims to explore the job satisfaction of those working-from-home in relation to work-life boundaries, before and during the quarantine period. Findings are useful for a deeper understanding of how new work arrangements influence tele-workers' perceptions of their quality of life. Results indicate that while before the pandemic, the job satisfaction of those working from home was increasing with the age of the respondent (the younger being more satisfied with working from home), that trend changed during quarantine, and job satisfaction increased significantly for people over 40. Additionally, working more hours before the pandemic is associated with lower job satisfaction scores during COVID-19 quarantine.